Determinantes das Exportações de países selecionados da América Latina (Argentina, Brasil e México): Modelos ARDL e NARDL - Cavessana, Letícia Vieira (2020)
This study develops an empirical investigation on the exports determinants for three selected Latin American countries – Brazil, Argentina and Mexico – for the period of the first quarter of 1997 to the fourth quarter of 2018. We estimated autoregressive distributed lags models (ARDL) and non-linear models (NARDL). The econometric methodology allows for the diagnostic of the existence of cointegration and for the short run adjustment through the Error Correction Model (ECM). The main results for the long run analysis of the ARDL and NARDL models indicate that higher (lower) exchange rate volatility are associated to lower (higher) exports. On the other hand, real effective exchange rate depreciations, improvements in terms of trade and increase in commodity price index beneficiate exports for all three countries. There is also evidence that exports in Mexico are negatively affected by exchange rate misalignment and positively by the income of the main trade partners. The NARDL models reveals robust results on the negative impact of exchange rate appreciations, mainly for Argentina. Finally, the results from the error correction model indicate that Brazilian exports have the highest speed of adjustment towards the long run equilibrium when facing short run shocks and Argentina has the lowest speed of adjustment.